Kesuksesan Manajemen Komunikasi dan Psikologi Nabi Muhammad SAW Dalam Mengatasi Masalah Keluarga - Sulidar Sulidar; Nawir Yuslem; Fadhilah Is; Uqbatul Khoir Rambe; T. Wildan (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The Success of Prophet Muhammad SAW Communication Management and Psychology in Overcoming Family ProblemsThis study discusses communication management and the psychology of the Prophet Muhammad SAW in overcoming family problems with a transdisciplinary approach. The research method is content analysis, which describes quantitatively, objectively, and systematically the contents of a communication. This research accumulates 7 primary and 6 secondary hadiths from Hadith literature references. The qualities of these hadiths are authentic, hasan and daif. There were 7 incidents of bullying, namely, First, Aisyah called Shafiyyah a Jew; Second, Aisyah insulted Shafiyyah's physique; Third, Hafshah called Shafiyah a Jew; Fourth, the Prophet's wives bullied Shafiyah because they were considered to have made an effort to create a self-image; Fifth, Aisyah again mentions the Jewish Shafiyah; Sixth, Aisyah bullied Khadijah as an older woman; Seventh, Zainab calls Shafiyyah a Jew. The Prophet's governance in this problem was with smiles, affectionate touches, close calls, dialogue, advice, reprimands, determining cases fairly, and breaking off interactions within a certain period. Research findings: The Prophet's problem-solving success was due to the Prophet's expertise in communication management and psychology. There are 6 principles of communication that the Prophet applied when interacting with his wives, namely qaulan ma'rufan (good rhetoric), qaulan sadīdan (correct), qaulan maysūran (easy to understand), qaulan karīman (respect the interlocutor), qaulan balīghan (practical), and qaulan layyinan (polite). In a psychological approach, the Prophet applied love language (words of affirmation, quality time, physical touch, acts of service, receiving gifts) to his family to build an everlasting love bond. When problems arose, the Prophet tried to solve them with psychodynamic, behavioristic, gestalt, counseling, and religious approaches. This proves that the Prophet is a role model in household management for humans